Superior silybin bioavailability of silybin-phosphatidylcholine complex in oily-medium soft-gel capsules versus conventional silymarin tablets in healthy volunteers* - Nahum Méndez-Sánchez; Miguel Dibildox-Martinez; Jahir Sosa-Noguera; Ramón Sánchez-Medal; Francisco J. Flores-Murrieta (BMC, 2019)
Abstract Background Fibrosis is a response to chronic liver disease that results in excessive accumulation of extracellular matrix proteins and formation of scar tissue. Fibrosis represents a clinical challenge of worldwide significance. Several studies have demonstrated that many natural products and herbal medicines have activity against liver fibrosis, and extracts of milk thistle such as silymarin and silybin are the natural compounds most commonly prescribed for liver diseases. Therefore, we sought to assess and compare the pharmacokinetic properties and bioavailability of silybin-phosphatidylcholine complex in oily-medium soft-gel capsules and conventional silymarin tablets in healthy Mexican volunteers. Methods We enrolled 23 healthy volunteers to participate in a prospective, balanced, blind, single-dose, two-way crossover study with a one-week washout period. Fasting participants received either 45 mg silybin-phosphatidylcholine complex or 70 mg silymarin to assess which formulation provided better bioavailability of silybin. Plasma was obtained and analysed for silybin concentration using a validated ultra-performance liquid chromatography-tandem mass spectroscopy method. Pharmacokinetic parameters were obtained by non-compartmental analysis and values were compared by analysis of variance for a crossover design. Ratios of maximum plasma drug concentration and area under the curve (AUC) were obtained and 90% confidence intervals were calculated. Results The 23 healthy subjects (11 women, 12 men) who participated in the study were aged 22-31 years old (average: 28), average weight 64.8 kg, height 1.65 m and body mass index 23.5 kg/m2. Plasma levels of silybin were higher after the administration of silybin-phosphatidylcholine complex capsules compared with that after conventional silymarin tablets (P <  0.0001). Conclusions The silybin-phosphatidylcholine complex in oily-medium soft-gel capsules seems to provide superior bioavailability. However, clinical studies must be performed to demonstrate its clinical relevance in the treatment of liver diseases. Trial registration NCT03440164; registered on November 11, 2016.